Numerical research of the retaining constructions during the reconstruction of the transport structures - Prusov, Dmitry (Transport, 2012)
The research analysis of interaction artificial retaining constructions with a non-uniform soil basis has been performed during the reconstruction of the transport structures. The mathematical model of soil semi-space research with the use of the nonlinear theory of elasticity is developed. The results of numerous researches of stress-strain state fencing constructions of the overpass in interaction with multilayer heterogeneous half-space and surfaces under the influence of band-pass loading are represented in the current paper.First Published Online: 21 Dec 2012